2014
DOI: 10.1111/jop.12246
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of lactate dehydrogenase enzyme activity in saliva and serum of oral submucous fibrosis patients

Abstract: This study provides additional rationale for the role of salivary LDH in the early diagnosis and prognosis of oral submucous fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
50
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 18 publications
3
50
1
Order By: Relevance
“…In the present study the level of salivary lactate dehydrogenase in toombak dippers was found higher than the level of the enzyme concentration in the control group , while the level of the enzyme in OSCC patients was found lower than the level in control group. The results of the present study agreed with the study held by Sivaramakrishnanet al 27 on oral submucous fibrosis when they reported lower level of enzyme concentration in OSCC patients group compared to control group.The results contradicted with the findings ofthe findings of Josti 28 , who reported an overall steadily increasing levels of enzyme concentration, matching the progress in cancer lesion.The results of the study are inconsistent with the findings of Lockshet al 29 , who reported statistically significant difference between the level in the control group, and the level in patients group.…”
Section: Uric Acid Levels In Serumsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study the level of salivary lactate dehydrogenase in toombak dippers was found higher than the level of the enzyme concentration in the control group , while the level of the enzyme in OSCC patients was found lower than the level in control group. The results of the present study agreed with the study held by Sivaramakrishnanet al 27 on oral submucous fibrosis when they reported lower level of enzyme concentration in OSCC patients group compared to control group.The results contradicted with the findings ofthe findings of Josti 28 , who reported an overall steadily increasing levels of enzyme concentration, matching the progress in cancer lesion.The results of the study are inconsistent with the findings of Lockshet al 29 , who reported statistically significant difference between the level in the control group, and the level in patients group.…”
Section: Uric Acid Levels In Serumsupporting
confidence: 93%
“…Shircant and Rashmi 26 revealed that are very few studies have been done in serum and saliva lactatedehydrogenase in patients with OSCC 27 .Salivary lactate dehydrogenase levels of the different groups in the present study ( Table 2) showed slight difference that was not statistically significant. In the present study the level of salivary lactate dehydrogenase in toombak dippers was found higher than the level of the enzyme concentration in the control group , while the level of the enzyme in OSCC patients was found lower than the level in control group.…”
Section: Uric Acid Levels In Serumcontrasting
confidence: 59%
“…The comparison of salivary LDH levels between OSMF and healthy subjects was statistically significant (p < 0.001). Our study findings were consistent with the study conducted by Sivaramakrishnan et al, 3 Kallalli et al, 1 Bhambal et al, 2 Shetty et al, 16 Rathore et al, 9 Pereira et al, 6 and Muralidhar et al 14 According to WHO 2005, oral leukoplakia is defined as a predominantly white patch or plaque that cannot be characterized clinically or pathologically as any other disorder; oral leukoplakia carries an increased risk of cancer development either in or close to the area of leukoplakia or elsewhere in the oral cavity or the head and neck region. 17 Malignant transformation rate of oral leukoplakia varies from 0.13 to 34%.…”
supporting
confidence: 94%
“…The LDH enzyme activity in OSMF is mainly related to following factors: Hypoxia, alteration in glycolysis, and fibrosis. 3 On comparing the serum LDH levels in OSMF groups and healthy controls in our study, we found that serum LDH levels in OSMF cases were greater than in healthy controls. This comparison was statistically significant (p < 0.001).…”
mentioning
confidence: 89%
See 1 more Smart Citation